The coastal waters of the south-east Bay of Biscay a dead-end for neustonic plastics. (August 2022) - Basurko, Oihane C.; Ruiz, Irene; Rubio, Anna; Beldarrain, Beatriz; Kukul, Deniz; Cózar, Andrés; Galli, Matteo; Destang, Théo; Larreta, Joana
Abstract: Numerical models point to the south-east Bay of Biscay as a convergence area for floating particles, including plastics. The few existing studies on plastic abundance in the area mainly focus on open waters and yet information on the coastal area is limited. To fill this gap, neustonic samples were taken along the coastal waters of the south-east Bay of Biscay (2017–2020) to define the spatial distribution of plastic abundances and composition. Results show an average plastic abundance of 739, 395 ± 2, 625, 271 items/km 2 (998 ± 4338 g/km 2 ). French waters were more affected, with five times higher plastic abundances than Spanish coasts. Microplastics represented 93 % of the total abundance of plastic items (28 % in weight), mesoplastics 7 % (26 %) and macroplastics 1 % (46 %). This study demonstrates that this area is a hotspot for plastic with levels in coastal waters similar to those in the Mediterranean Sea or other litter aggregation areas. Highlights: The south-east coast of Bay of Biscay is a convergence area for plastics. Plastic abundance in the studied area was medium-high based on published literature. Abundances in French waters were substantially higher compared with Spanish waters. Plastic fragments and transparent microplastics were the most abundant plastic items. A strong positive correlation was found between micro and mesoplastic abundances.